Prevalence and risk factors of Enterobiasis among pre-school children in selected barangays in Dumaguete City, Philippines - Villordon, Mae Brigitt Bernadel L. (Silliman Journal, 2008)
The study was an explanatory step, a rapid assessment of the prevalence of Enterobius vermicularis (pinworm) and its risk factors among pre-school children in selected barangays (villages) in Dumaguete City, Philippines, so that intervention that would contribute to improving the health status of pre-school children in the city may be proposed. A map showing Enterobius vermicularis infection "hotspots" was generated. The prevalence and risk factors of enterobiasis among preschool children were determined through questionnaire survey that had three components: the socio-demographic profile, environmental factors, and the KAP (Knowledge, Attitude and Practice) of respondents. Microscopic examination of Enetrobius vermicularis was done between December 2006 to January 2007 using the perianal tape swab method taken from the target population. A total of 276 children from eight barangays were examined from Enterobius vermicularis. Results of the examination revealed a 2.50% overall prevalence, with a range of 0.00% to 11.11%. Eight children were found positive for other parasites such as Ascaris lumbricoides and Isospora belli. The geographical extent of the enterobiasis indicated a relatively high prevalence on the southwestern side of the publican (municipality centre) where the sear of government is located. Household environmental scores for the barangays covered by this survey ranged from 63.33% to 71.33%. An evaluation of the day care centre environs yielded an environmental score ranging from 75% to 96.67%. Knowledge scores ranged from 36% to 66%. Attitude towards the disease scores ranged from 73.30% to 81.64%. there are indications that the relationship between KAP, environmental scores, and prevalence is inverse. The low prevalence can be attributed to the relatively high environmental and KAP scores. However, there are barangays that had less than 50% scores, due to low education and negative attitudes towards the disease. This should be prioritised in terms of interventions to keep the prevalence level to a minimum if not eradicated. There are also indicators that prevalence of enterobiasis increases with an increasing day care class size. However, correlation analysis shows that this was not significant. The low prevalence of enterobiasis could also be attributed to medications made available to the community by non-governmental organisations as well as the local government.